Delimiting species, revealing cryptic diversity, and population divergence in Qinghai‐Tibet Plateau weevils through DNA barcoding - Jinliang Ren; Li Ren; Runzhi Zhang (Ecology and Evolution, 2024)
Abstract The Leptomias group represents one of the most diverse taxonomic group of weevils in the Qinghai‐Tibet Plateau and its adjacent areas. Despite the potential of hidden diversity, relatively few comprehensive studies have been conducted on species diversity in this taxonomic group. In this study, we performed DNA barcoding analysis for species of the Leptomias group using a comprehensive DNA barcode dataset that included 476 sequences representing 54 morphospecies. Within the dataset, our laboratory contributed 474 sequences, and 390 sequences were newly generated for this study. The average Kimura 2‐parameter distances among morphospecies and genera were 0.76% and 19.15%, respectively. In 94.4% of the species, the minimum interspecific distances exceeded the maximum intraspecific distances, indicating the presence of barcode gaps in most species of Leptomias group. The application of Automatic Barcode Gap Discovery, Assemble Species by Automatic Partitioning, Barcode Index Number, Bayesian Poisson tree processes, jMOTU, and Neighbor‐joining tree methods revealed 45, 45, 63, 54, and 55 distinct clusters representing single species, respectively. Additionally, a total of four morphospecies, Leptomias kangmarensis, L. midlineatus, L. siahus, and L. sp.9RL, were found to be assigned to multiple subclade each, indicating the geographical divergences and the presence of cryptic diversity. Our findings of this study demonstrate that Qinghai‐Tibet Plateau exhibits a higher species diversity of the Leptomias group, and it is imperative to investigate cryptic species within certain morphospecies using integrative taxonomic approaches in future studies. Moreover, the construction of a DNA barcode reference library presented herein establishes a robust foundational dataset to support forthcoming research on weevil taxonomy, phylogenetics, ecology, and evolution.